2020
DOI: 10.1016/j.xjon.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia in patients readmitted after open cardiac surgical procedures: A case series

Abstract: Objectives: Heparin-induced thrombocytopenia (HIT) is an immune-mediated complication that occurs in a small percentage of patients exposed to heparin. Concerns of HIT are particularly high in patients undergoing cardiac procedures requiring cardiopulmonary bypass, as they are exposed to high doses of heparin intraoperatively. Our aim was to identify and assess the hospital courses of patients who were diagnosed with HIT during readmission following cardiac surgery.Methods: A retrospective review of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Evaluation of this case series of Catalano and colleagues emphasizes that a thrombotic postoperative event is a potential indicator for HITTS during readmission even in the absence of thrombocytopenia. 3 Furthermore, provoking these patients with heparin worsens the situation, as demonstrated in this case series, in which the thrombocytopenia (and likely the thrombosis) was exacerbated by the administration of heparin. Alternative anticoagulants to heparin should be used pending a more definitive diagnosis.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Evaluation of this case series of Catalano and colleagues emphasizes that a thrombotic postoperative event is a potential indicator for HITTS during readmission even in the absence of thrombocytopenia. 3 Furthermore, provoking these patients with heparin worsens the situation, as demonstrated in this case series, in which the thrombocytopenia (and likely the thrombosis) was exacerbated by the administration of heparin. Alternative anticoagulants to heparin should be used pending a more definitive diagnosis.…”
mentioning
confidence: 66%
“… 2 Awareness of this phenomenon in postoperative cardiac surgery patients is heightened by the case series reported by Catalano and colleagues in this issue of the Journal . 3 Their retrospective analysis spanned 28 months at a busy cardiac surgery center and included 2496 patients undergoing cardiac surgery with cardiopulmonary bypass (CPB). During that time, 351 patients (14%) were readmitted within 30 days, 6 of whom (1.7%) were diagnosed with HIT confirmed by both positive heparin-PF4 antibodies (on enzyme-linked immunosorbent assay) and a positive serotonin release assay.…”
mentioning
confidence: 99%
“…HIT is rarely observed in patients in the ICU (0.5-1%); Catalona et al reported a rate of only 0.2% (6/2483) of patients after open-heart surgery. 4,18 Therefore, it is necessary to consider other factors that may more frequently lead to the development of thrombocytopenia. In logistic regression analysis, we found that age ≥80 years increased the risk of developing moderate-severe thrombocytopenia ninefold compared with age 18-39 years.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin-induced thrombocytopenia suggests the obligatory association of absolute or relative thrombocytopenia, yet, as shown by Catalano and coworkers, 3 HIT may still be present without thrombocytopenia. In 5 of 6 patients readmitted for thromboembolism after cardiopulmonary bypass, readmission platelet counts were not significantly different from the preoperative values.…”
mentioning
confidence: 89%